Cultural Heritage Tourism Management in Pashupatinath Area - Nyaupane, Pashupati (Nepalese Culture, 2019)
Heritage represents irreplaceable resources for the tourism industry so conservation is a vital component of their management. Throughout the world, the tourism industry has been an economic generator including conserving the heritage sites. Today, tourism has been considered to have greater socio economic values. Thus Pashupatinath area, with its rich cultural heritage, has great potential to be tapped through cultural heritage tourism. Pashupatinath area is known for its rich cultural heritage, but lack of proper tourism guidelines in the areas has not been able to showcase its potential. Thus, the paper tries to bring the importance of heritage tourism in the core area of Pashupatinath and its vicinity into limelight. The paper addresses the need of improvement in management, information and development in infrastructure. Moreover it covers the approach of conservation of tangible and intangible cultural heritage. This article examines the significance and value of Pashupatinath area as a cultural heritage tourism destination. This research identifies numerous issues related to cultural heritage tourism management in Pashupatinath area and its cultural heritage tourism products, coordination among stakeholders and interpretation. It explores the current management situation of Pashupati area and provides the suggestion for the betterment of cultural heritage tourism in Pashupatinath area. The paper helps to relate the tourism industry with the economic growth of Pashupatinath area.